1996
DOI: 10.2172/418980
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Alaska North Slope gas utilization options

Abstract: Under DOE Idaho Operations Office Contract DE-AC07-941D13223t DISCLAIMERPortions of this document may be illegible in electronic image products. Images are produced from the best available original document. ECONOMICS OF ALASKA NORTH SLOPE GAS UTILIZATION OPTIONS ABSTRACTThe recoverable natural gas available for sale in the developed and known undeveloped fields on the Alaskan North Slope (ANS) total about 26 trillion cubic feet (TCF), including 22 TCF in the Prudhoe Bay Unit (PBU) and 3 TCF in the undeveloped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The capital cost of a GTL plant is estimated at between $25,000 per daily barrel (DBL) capacity and $35,00O/DBL (Thomas et al, 1996). Current industry average for a US gulf coast plant puts the capital cost at about $24,000 / DBL.…”
Section: Plant Costmentioning
confidence: 99%
See 1 more Smart Citation
“…The capital cost of a GTL plant is estimated at between $25,000 per daily barrel (DBL) capacity and $35,00O/DBL (Thomas et al, 1996). Current industry average for a US gulf coast plant puts the capital cost at about $24,000 / DBL.…”
Section: Plant Costmentioning
confidence: 99%
“…The two most promising options are: (i) transportation of the gas via a new gas pipeline, called as the Trans-Alaska-Gas-System (TAGS) followed by Liquefaction to LNG and then to Pacific-Rim markets via LNG tankers, and (ii)conversion of the gas to GTL products followed by transportation via the existing Trans-Alaska-Pipeline-System (TAPS). In a recent study by Robertson et al (1996), it was concluded that the TAGSLNG and the GTL options appear economically promising and warrant consideration in the decision-making process. Moreover, the future market for ANS-LNG is less certain than a potential market for GTL products.…”
Section: Introductionmentioning
confidence: 99%